Deception and Emotional Manipulation in Online Romance Scams: A Systematic Literature Review - Himmatul Husna; Setyadi Ari Murtopo; Charanjit Kaur; Myrtati Dyah Artaria (Fakultas of Psychology, Universitas Muria Kudus, 2026)
Online romance scams are one of the most common crimes that have emerged alongside the development of technology. Romantic fraud is not merely a financial crime but also an exploitation of the victim's emotional vulnerability. This crime is facilitated by anonymity and the ability to interact without having to meet in person. Scammers deliberately build false identities and gradually develop emotional bonding to obtain financial gain without appearing to be deceitful. This study uses a systematic literature review methods with reference to the PRISMA protocol to filter studies published between 2010-2025 related to psychological characteristics commonly found in romance scammers. The findings state that scammers present themselves with traits that are recognized by the public as a good standards. They carefully construct stories in a difficult settings to attract victim sympathy, so the victims willingly send them money. The actions continue over a long period of time because the scammers do not feel guilty. Instead, they defend themselves with various manipulative statement and moral rationalizations. These results emphasize the need for collaborative prevention efforts across jurisdictions, considering that this crime is a part of transnational crime. Penipuan asmara daring merupakan salah satu kejahatan paling umum yang muncul seiring pesatnya perkembangan teknologi. Penipuan asmara bukan hanya kejahatan finansial, tetapi juga eksploitasi kerentanan emosional korban. Kejahatan ini difasilitasi oleh anonimitas dan kemampuan untuk berinteraksi tanpa harus bertemu langsung. Penipu sengaja membangun identitas palsu dan secara bertahap mengembangkan ikatan emosional untuk mendapatkan keuntungan finansial tanpa terlihat menipu. Studi ini menggunakan metode tinjauan literatur sistematis dengan mengacu pada protokol PRISMA untuk menyaring studi yang diterbitkan antara tahun 2010-2025 yang berkaitan dengan karakteristik psikologis yang umum ditemukan pada penipu asmara. Temuan menunjukkan bahwa penipu menampilkan diri dengan sifat-sifat yang diakui oleh publik sebagai standar yang baik. Mereka dengan cermat menyusun cerita dalam situasi yang sulit untuk menarik simpati korban, sehingga korban dengan rela mengirimkan uang kepada mereka. Tindakan tersebut berlanjut dalam jangka waktu yang lama karena penipu tidak merasa bersalah. Sebaliknya, mereka justru membela diri dengan berbagai pernyataan manipulatif dan rasionalisasi moral. Hasil ini menekankan perlunya upaya pencegahan kolaboratif lintas yurisdiksi, mengingat kejahatan ini merupakan bentuk dari kejahatan transnasional.